2018
DOI: 10.1039/c7ra13062g
|View full text |Cite
|
Sign up to set email alerts
|

Design of triphasic poly(lactic-co-glycolic acid) nanoparticles containing a perfluorocarbon phase for biomedical applications

Abstract: The influence of different synthesis parameters on the characteristics of polymeric particles with a third perfluorocarbon phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…A PFCE encapsulation of 20–40 wt% (33 ± 11 wt% (number of batches N = 79)) was demonstrated by NMR spectroscopy (compare Table S2, Supporting Information, for some examples). We found that these nanoparticles, apart from being suitable for 19 F MRI, also generate acoustic contrast and can be imaged using standard ultrasound B‐mode imaging (Figure c). Moreover, the acoustic contrast lasts at least a few hours with no signs of degradation, allowing for long‐term imaging over a course of 48 h at least, as we show later in this study ( Figure c).…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…A PFCE encapsulation of 20–40 wt% (33 ± 11 wt% (number of batches N = 79)) was demonstrated by NMR spectroscopy (compare Table S2, Supporting Information, for some examples). We found that these nanoparticles, apart from being suitable for 19 F MRI, also generate acoustic contrast and can be imaged using standard ultrasound B‐mode imaging (Figure c). Moreover, the acoustic contrast lasts at least a few hours with no signs of degradation, allowing for long‐term imaging over a course of 48 h at least, as we show later in this study ( Figure c).…”
Section: Resultssupporting
confidence: 66%
“…The nanoparticles are synthesized using a miniemulsion formulation technique . They consist of a PLGA matrix loaded with PFCE and are stabilized with poly(vinyl alcohol) (PVA) ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations